Growth of CdS thin films by chemical bath deposition technique - Be, Xuan Hop (H. : ĐHQGHN, 2017)
The structural, morphological and optical properties of CBD deposited CdS thin films have been studied by varying the processing parameters and the Cd/S ratio of the starting precursors in order to better understand the growth conditions. The films were characterized by X-ry diffration, SEM, Raman, and photoluminescence spectroscopy. SRD patterns show that asdeposited CdS films were polycrystalline. The fact that the symmetry - dependent Raman bands of the CdS thin films under investigation did not appear indicates the poor preferential orientation of as-deposited CdS crystallites, which is in accordance with the measured XRD pattern.